2010
DOI: 10.1002/cjce.20414
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium configurations of drops attached to spheres immersed in a uniform laminar flow

Abstract: A computational fluid dynamics model has been developed to study the behaviour of a solid particle partially coated by an oil film and immersed in a uniform aqueous flow, to predict the equilibrium configurations of the film. The flow equations are solved using a finite volume approach, and the oil/water interface is captured using a Volume-of-Fluid method in 2D spherical coordinates. At Ca < < 1, shear forces are negligible, as interfacial tension maintains the oil film as a spherical cap. As Ca approaches 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…7b reveals that the second transition occurs around a capillary number close to 1. Fan et al conducted Computational fluid dynamic (CFD) simulations on the removal of an oil film from a 100-lm spherical particle fixed in space and subject to a constant flow field under different interfacial tensions and oil loadings [33]. Fan et al found that there was a critical capillary number, close to 1, when the oil film was unstable and detached from the particle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7b reveals that the second transition occurs around a capillary number close to 1. Fan et al conducted Computational fluid dynamic (CFD) simulations on the removal of an oil film from a 100-lm spherical particle fixed in space and subject to a constant flow field under different interfacial tensions and oil loadings [33]. Fan et al found that there was a critical capillary number, close to 1, when the oil film was unstable and detached from the particle.…”
Section: Discussionmentioning
confidence: 99%
“…Although no experiment was carried out beyond particle-based Capillary numbers of 1 (Fig. 8b, d), it is expected that at those conditions the film would not be emulsified, but sheared off the surface, as predicted fluid dynamics calculations [33,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, there remains a lack of studies on the hydrodynamics of separation from an oil-coated particle. The work presented here complements the research of Fan et al [19] and Smith and Van de Ven [16]. We present an experimental study of the separation of oil from an oil-coated sphere in free fall through an immiscible viscous fluid, and complementary numerical results.…”
Section: Fig 1 An Oil-coated Particle Falling Through An Aqueous Somentioning
confidence: 61%
“…The CFD study of Fan et al [19] is most closely related to the work presented here. A model of an oil-coated particle immersed in an axisymmetric laminar flow was developed.…”
Section: Fig 1 An Oil-coated Particle Falling Through An Aqueous Somentioning
confidence: 63%